Unveiling Druggable Pockets by Site-Specific Protein Modification: Beyond Antibody-Drug Conjugates - Martínez, Dailén G.; Hüttelmaier, Stefan; Bertoldo, Jean B. (Frontiers in Chemistry, 2020)
Site-specific modification approaches have been extensively employed in the development of protein-based technologies. In this field, stability and activity integrity are the envisioned features of chemically modified proteins. These methods are especially used in the design of antibody-drug conjugates (ADCs). Nevertheless, a biochemical feature of the target protein in these reactions is often overlooked, residue specificity. Usually, in the course of developing chemical probes to modify a protein of interest (POI), specific amino acids are selected due to their reactivity. It is not critical which residue is modified as long as its modification does not compromise the POI’s activity. However, no attention is paid as to why certain residues are preferentially modified over others. Physicochemical and structural constraints are often involved in the reactivity of the residue and account for the preferential modification. We propose that site-specific protein modification approaches can be applied beyond the development of ADCs or protein-drug conjugates, and used as a tool to reveal therapeutically relevant residues. By preferentially modifying certain side chains in the POI, chemical probes can uncover new binding motifs to investigate. Here we describe methods for protein modification, and how some pitfalls in the field can be turned into tools to reveal and exploit druggable pockets. Thus, allowing the design of innovative inhibitors, against disease-relevant POIs. We discuss methodologies for site-specific modification of lysine, tryptophan, cysteine, histidine and tyrosine and comment on instances where the modified residues were used as targets for functionalization or drug design.